Lactiplantibacillus plantarum fermentation boosts antioxidant and antibacterial effects in Allium species, potentially replacing chicken antibiotics - Hai, PV; Hoang, Thi Anh Phuong; Pham, Hoang Son Hung; Na, Thi; Ngo, Huu Lai; Ho , Thi Dung; Nguyen, Xuan Hoa (Journal of the Hellenic Veterinary Medical Society, 2025)
This study aimed to enhance the antioxidant and antibacterial properties of extract of purple onion (OE, Allium cepa L.) and chive (CE, Allium schoenoprasum) bulbs through Lactobacillus plantarum-mediated fermentation regarding their antioxidant capacity, antibacterial activity. Among seven isolates from local free-range chicken feces, LA24 was selected for its highest survival rate (89%) against the antibacterial activities of both OE and CE. It was identified as L. plantarum 1582 through 16S rRNA gene sequencing and was utilized for the CE and OE fermentation study. Fermentation significantly increased the total phenolic content (TPC) of both extracts. Specifically, the TPC of fermented purple onion extract (FOE) increased from 4,16 to 11,63 mg gallic acid equivalents (GAE)/g, while the TPC of fermented chive extract (FCE) increased from 8,51 to 23,45 mg GAE/g. Furthermore, both FOE and FCE exhibited enhanced antioxidant activities. The DPPH radical scavenging activity, measured by IC50 values, improved from 17,14 to 11,21 mg/mL for FOE and from 4.63 to 3,18 mg/mL for FCE. Both extracts also demonstrated increased reducing power following fermentation. Importantly, FCE showed stronger antibacterial activity against Escherichia coli and Salmonella spp., key pathogens associated with diarrhea in broiler chickens, compared to FOE. In vivo studies in chickens confirmed the transient colonization potential of L. plantarum 1582 in the chicken gut. These findings suggest that fermented Allium extracts, particularly FCE, hold promise as natural antibiotic alternatives in poultry feed, contributing to improved antioxidant status and disease resistance.